Furious snarling: Teeth-exposure and anxiety-related attentional bias towards angry faces. - Benedikt Emanuel Wirth; Dirk Wentura (PLoS ONE, 2018)
Dot-probe studies consistently show that high trait anxious individuals have an attentional bias towards threatening faces. However, little is known about the influence of perceptual confounds of specific emotional expressions on this effect. Teeth-exposure was recently recognized as an important factor for the occurrence of attentional bias towards angry faces in a closely related paradigm (the face-in-the-crowd paradigm). Therefore, we investigated the effect of exposed teeth on attentional bias towards angry faces in the dot-probe task. Participants (N = 74) were asked to classify probe stimuli that were preceded by two simultaneously presented face cues, one angry and the other neutral. Half of the angry faces had exposed teeth, the other half had concealed teeth. Afterwards, participants completed the trait anxiety scale of the STAI. For angry faces with non-exposed teeth, we found the expected positive correlation (r = .441) of trait anxiety with the attentional bias score (reaction times for probes replacing the neutral face minus reaction times for probes replacing the angry face). However, we found no influence of trait anxiety on attentional bias towards angry faces with exposed teeth. These results suggest that natural low-level stimulus confounds of emotional faces like exposed teeth can affect the manifestation of anxiety-related attentional biases towards angry faces in the dot-probe task.